Forecasting CO2 emissions in the Persian Gulf States - F.A. Olabemiwo; G.I. Danmaliki; T.A. Oyehan; B.S. Tawabini (Global Journal of Environmental Science and Management)
The Persian Gulf States (Bahrain. Iran, Iraq, Qatar, Saudi Arabia, Kuwait and United Arab Emirate) have dominated the oil and gas sector since the discovery of oil in the region. They are the world largest producers of crude oil, producing about 35 and 25 percent of the world natural gas and crude oil respectively. The use of fossil fuels is directly linked to the release of CO2 into the environment. CO2 accounts for 58.8 percent of all greenhouse gases released via human activities, consequently, presenting a malign impact on the environment through climate change, global warming, biodiversity, acid rain and desertification among others. Due to its importance, the data on CO2 emission obtained from US EIA from 1980 – 2010 was regressed using least square techniques and projections were made to the year 2050. Results indicated that each country’s p-value was less than 0.05 which implies that the models can be used for predicting CO2 emissions into the future. The data shows the emission of CO2 by countries from the highest to the lowest in 2016 as: Iran (590.72 Mtonnes; 7.58 tonnes of CO2/person) > Saudi Arabia (471.82 Mtonnes; 18 tonnes of CO2/person) > UAE (218.58 Mtonnes; 41.31 tonnes of CO2/person) > Iraq (114.01 Mtonees; 3.71 tonnes of CO2/person) > Kuwait (92.58 Mtonnes; 36.31 tonnes of CO2/person) > Qatar (68.26 Mtonnes; 37 tonnes of CO2/person) > Bahrain (33.16 Mtonnes; 27.5 tonnes of CO2/person)". The sequence from the country with highest emission (Iran) to the country with lowest emission (Bahrain) will remain the same until 2050. A projection depicting a 7.7 percent yearly increase in CO2 emission in the Persian Gulf States.